Special education past, present, and future perspectives from the field - Cook, Bryan G.; Tankersley, Melody; Landrum, Timothy J. (Advances in learning and behavioral disabilities, 2014)
This volume explores serious challenging behavior in schools, with an emphasis on promising and research-based approaches to dealing with such behavior. Topics include what we know about (a) the nature and extent of the problem (e.g., rates of aggression, violence, and noncompliance in schools); (b) addressing extreme forms of noncompliance; (c) dealing with serious disruptive behavior; (d) violence prevention programs; (e) schoolwide response to aggression and violence; (f) issues of covert antisocial behavior (e.g., vandalism, truancy, theft); (g) functional behavioral assessment and function-based interventions; (h) legal and policy considerations in disciplining students with disabilities; and (i) promising and needed avenues for further research.